A NEW METHOD FOR THE PREPARATION OF HYDRAZIDES OF SUBSTITUTED GAMMA-HYDROXYBUTANOIC ACIDS (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
A method providing a high yield (80–94%) for producing gamma-hydroxy-butanoic acids hydrazides by the interaction of various representatives of cyclic esters with 85% hydrazine hydrate has been elaborated. It has been established that the introduction of a gamma-hydroxypropyl residue into the hydrazides composition results in new biological properties.
Keywords: gamma-hydroxycarboxylic acid hydrazides; cyclic esters